Regulating the Digital Economy - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2021)
This editorial comes in three parts: some observations on the growing need to regulate the digital economy more effectively; a brief introduction to the papers in this issue; and some updates on the editorial team that produces the Journal of Telecommunications and the Digital Economy.